Friction behaviors in the metal cutting process: state of the art and future perspectives. (1st March 2023) - Liang, Xiaoliang; Liu, Zhanqiang; Wang, Bing; Wang, Chunjin; Cheung, Chi Fai
Abstract: Material removal in the cutting process is regarded as a friction system with multiple input and output variables. The complexity of the cutting friction system is caused by the extreme conditions existing on the tool–chip and tool–workpiece interfaces. The critical issue is significant to use knowledge of cutting friction behaviors to guide researchers and industrial manufacturing engineers in designing rational cutting processes to reduce tool wear and improve surface quality. This review focuses on the state of the art of research on friction behaviors in cutting procedures as well as future perspectives. First, the cutting friction phenomena under extreme conditions, such as high temperature, large strain/strain rates, sticking–sliding contact states, and diverse cutting conditions are analyzed. Second, the theoretical models of cutting friction behaviors and the application of simulation technology are discussed. Third, the factors that affect friction behaviors are analyzed, including material matching, cutting parameters, lubrication/cooling conditions, micro/nano surface textures, and tool coatings. Then, the consequences of the cutting friction phenomena, including tool wear patterns, tool life, chip formation, and the machined surface are analyzed. Finally, the research limitations and future work for cutting friction behaviors are discussed. This review contributes to the understanding of cutting friction behaviors and the development of high-quality cutting technology. Highlights: Friction behaviors in metal cutting processes were reviewed. Elevated temperature, large strain/strain rate, extreme deformation, and sticking–sliding state were analyzed as characteristics of contact interfaces. Theoretical models, simulation application, influencing factors, and consequences of cutting friction behaviors were discussed. Research limitations and future work for friction behaviors were put forward.